Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/2167702620906148
|View full text |Cite
|
Sign up to set email alerts
|

Do Cognitive Tasks Reduce Intrusive-Memory Frequency After Exposure to Analogue Trauma? An Experimental Replication

Abstract: Cognitive task interventions that interfere with visuospatial working memory during the memory consolidation window hold promise for reducing intrusive memories in trauma-exposed people. Our study provides an independent replication study to test and verify findings that have primarily originated from a single research group. We hypothesized that participants engaging in a visuospatial task (cognitive task intervention including Tetris or D-Corsi) following a trauma-film paradigm (TFP) would report fewer intru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 56 publications
(120 reference statements)
2
17
0
Order By: Relevance
“…Following previous research (Badawi et al, 2020;Deeprose et al, 2012;Holmes et al, 2009;Holmes, James, et al, 2010;Lau-Zhu et al, 2019), baseline measures were completed at the start of the experiment on key clinical/cognitive dimensions that have been associated with increased risk for intrusive memories, including depression and anxiety (e.g., Brewin et al, 2010;Holmes et al, 2016), trauma history (e.g., Ozer et al, 2003), and mental imagery use (e.g., Kosslyn, 2005;Morina et al, 2013), to check for successful random assignments and rule these out as potential confounds.…”
Section: Overview Of the Current Experimentsmentioning
confidence: 99%
“…Following previous research (Badawi et al, 2020;Deeprose et al, 2012;Holmes et al, 2009;Holmes, James, et al, 2010;Lau-Zhu et al, 2019), baseline measures were completed at the start of the experiment on key clinical/cognitive dimensions that have been associated with increased risk for intrusive memories, including depression and anxiety (e.g., Brewin et al, 2010;Holmes et al, 2016), trauma history (e.g., Ozer et al, 2003), and mental imagery use (e.g., Kosslyn, 2005;Morina et al, 2013), to check for successful random assignments and rule these out as potential confounds.…”
Section: Overview Of the Current Experimentsmentioning
confidence: 99%
“…Laboratory studies comparing the cognitive task intervention to control conditions have demonstrated that it results in a reduction in the number of intrusive memories over one week (e.g., Holmes et al, 2009;Holmes et al, 2010). This finding has been replicated by an independent research group (Badawi et al, 2019). We emphasise that this is a multi-component intervention (reminder cue followed by visuospatial computer game play "Tetris" with mental rotation instructions)-it is not "just playing Tetris".…”
Section: Cognitive/behavioural Levelmentioning
confidence: 72%
“…Moreover, many reported zero intrusions (49/200) in the baseline phase prior to allocation to condition, requiring removal from the final analysis. This step does not appear to have been necessary to apply in previous studies, and even after the removals of the ‘zero intrusions’, the control group mean is still lower than the control group means in studies by Asselbergs et al ( 2018 ), Badawi, Berle, Rogers, and Steel ( 2020 ) and Kessler et al ( 2020 ). While Asselbergs et al ( 2018 ) and Badawi et al ( 2020 ) are both studies where the intervention was given at an earlier time frame than the current one, the control group should be comparable.…”
Section: Discussionmentioning
confidence: 85%
“…This step does not appear to have been necessary to apply in previous studies, and even after the removals of the ‘zero intrusions’, the control group mean is still lower than the control group means in studies by Asselbergs et al ( 2018 ), Badawi, Berle, Rogers, and Steel ( 2020 ) and Kessler et al ( 2020 ). While Asselbergs et al ( 2018 ) and Badawi et al ( 2020 ) are both studies where the intervention was given at an earlier time frame than the current one, the control group should be comparable. A possible explanation for this is that the films were shown on a PC which is smaller than the screen used by James et al ( 2015 ) (100 cm × 133 cm), and although the film was the same as James et al used, it was a copy and the visual and audio quality was reduced, perhaps thereby also reducing the film’s impact.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation